SERIES: ECONOMICS APPLIED TO PROCESS ENGINEERING (Part 3). OPERATING COST MANAGEMENT IN A COMPANY WITH MULTIPLE PRODUCTS - Porlles L., José A. (2005)
Each time is expanded the fan of businesses that diversify its product lines as a form to face the competence and to diversify its risk. In reality this situation does not assure the success of the organization. It is possible in certain circumstances to reduce, to eliminate or to prompt some product line. In this third part a cost-volume-utilities (C-V-U) analysis model is proposed for the management of the costs in a business with several production lines.